High folate levels are not associated with increased malaria risk but with reduced anaemia rates in the context of high‐dosed folate supplements and intermittent preventive treatment against malaria in pregnancy with sulphadoxine–pyrimethamine in Benin. Issue 6 (21st May 2018) - Moya‐Alvarez, Violeta; Ouédraogo, Smaila; Accrombessi, Manfred; Cot, Michel
Abstract: Objectives: To investigate whether high‐dosed folate supplements might diminish the efficacy of malaria intermittent preventive treatment in pregnancy (IPTp) with sulphadoxine–pyrimethamine (SP) in a cohort of pregnant women in Benin, where malaria is holoendemic. Methods: We followed 318 women during the entire pregnancy and analysed haematological and Plasmodium falciparum indicators in the context of an intermittent preventive treatment trial in Benin. During the follow‐up, women received two‐dose IPTp (1500/75 mg of SP per dose) at the maternity clinic and 600 mg of albendazole, 200 mg ferrous sulphate and 5 mg folic acid per day for home treatment. Results: High folate levels were not associated with increased malaria risk (adjusted OR (aOR) = 0.51 (95% CI: 0.17; 1.56, P ‐value = 0.24)), nor with increased P. falciparum density (beta coefficient = −0.26 (95% CI: −0.53; 0.02), P ‐value = 0.07) in a randomised trial of IPTp in Benin. On the contrary, higher iron levels were statistically associated with increased odds of a positive blood smear (aOR = 1.7 95% CI (1.2; 2.3), P ‐value < 0.001) and P. falciparum parasite density (beta coefficient = 0.2 95% CI (0.1; 0.3), P ‐value < 0.001). High folate levels were statistically associated with decreased odds of anaemia (aOR = −0.30 95% CI (0.10; 0.88), P ‐value = 0.03). Conclusions: High folate levels are not associated with increased malarial risk in a prospective longitudinal cohort in the context of both iron and high‐dosed folate supplements and IPTp. They are associated with reduced risk of anaemia, which is particularly important because iron, also given to treat anaemia, might be associated with increased malaria risk.